2015
DOI: 10.1093/toxsci/kfv016
|View full text |Cite
|
Sign up to set email alerts
|

DT-Diaphorase Prevents Aminochrome-Induced Alpha-Synuclein Oligomer Formation and Neurotoxicity

Abstract: It was reported that aminochrome induces the formation of alpha synuclein (SNCA) oligomers during dopamine oxidation. We found that DT-diaphorase (NQO1) prevents the formation of SNCA oligomers in the presence of aminochrome determined by Western blot, transmission electron microscopy, circular dichroism, and thioflavin T fluorescence, suggesting a protective role of NQO1 by preventing the formation of SNCA oligomers in dopaminergic neurons. In order to test NQO1 protective role in SNCA neurotoxicity in cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 43 publications
0
51
0
1
Order By: Relevance
“…Aminochrome interacts with human α-synuclein, inducing and stabilizing the formation of neurotoxic oligomers (Muñoz et al, 2015; Norris et al, 2005). Recently, by using a rat cell line with stable over-expression of wild type α-synuclein and a siRNA against the DT-diaphorase enzyme, it has been demonstrated that the neurotoxicity of α-synuclein oligomers depends on the silencing of DT-diaphorase enzyme (Muñoz et al, 2015).…”
Section: Iron In Da Oxidationmentioning
confidence: 99%
See 4 more Smart Citations
“…Aminochrome interacts with human α-synuclein, inducing and stabilizing the formation of neurotoxic oligomers (Muñoz et al, 2015; Norris et al, 2005). Recently, by using a rat cell line with stable over-expression of wild type α-synuclein and a siRNA against the DT-diaphorase enzyme, it has been demonstrated that the neurotoxicity of α-synuclein oligomers depends on the silencing of DT-diaphorase enzyme (Muñoz et al, 2015).…”
Section: Iron In Da Oxidationmentioning
confidence: 99%
“…Recently, by using a rat cell line with stable over-expression of wild type α-synuclein and a siRNA against the DT-diaphorase enzyme, it has been demonstrated that the neurotoxicity of α-synuclein oligomers depends on the silencing of DT-diaphorase enzyme (Muñoz et al, 2015). This enzyme is a flavoenzyme that catalyzes the two-electron reduction of aminochrome to leukoaminochrome, thus preventing the formation of neurotoxic α-synuclein oligomers induced by aminochrome.…”
Section: Iron In Da Oxidationmentioning
confidence: 99%
See 3 more Smart Citations